Kyai's Leadership and Strategic Management in Islamic Boarding Schools: Balancing Culture and Change, a Case Study of Al-Mashduqiah - Sudarmanto, Totok; Hepni; Abd. Muhith; Samsul Arifin; Sumarsi; Desy Salma Aeni (Mimbar Agama Budaya, 2025)
This study explores how the kiai at Pondok Pesantren Modern Al-Mashduqiah integrates spiritual leadership with strategic management practices to maintain pesantren identity while adapting to modernization and digital transformation. Using a qualitative case study approach, data were collected through in-depth interviews with 12 key informants, participant observation, and document analysis. The findings highlight four key themes: first, the kiai upholds organizational culture through sufistic values like sincerity and discipline; second, strategic planning is participatory, involving senior teachers and administrative staff; third, selective adoption of digital innovations, such as e-learning modules and online monitoring, enhances efficiency while preserving cultural authenticity; and fourth, the kiai's dual role as both spiritual guide and manager fosters an adaptive, cohesive organizational climate. The study offers insights into value-based strategic leadership in Islamic education and provides practical recommendations for improving governance and digital integration in pesantren.